A detailed inventory of linguistically and culturally sensitive speech- and language assessment material, available to speech- language therapists working in South Africa - Groenewald, Emily (University of Pretoria, 2021)
Mini Dissertation (BCommunication Pathology)--University of Pretoria, 2006.